High-dose phenylephrine increases meningeal blood flow through TRPV1 receptor activation and release of calcitonin gene-related peptide - Dux, Mária; Babes, Alexandru; Manchen, Jessica; Sertel-Nakajima, Julika; Vogler, Birgit; Schramm, Jana; Meßlinger, Karl (European Journal of Pain, 2019)
Background: The α1-adrenoceptor agonist, phenylephrine, is used at high concentrations as a mydriatic agent and for the treatment of nasal congestion. Among its adverse side-effects transient burning sensations are reported indicating activation of the trigeminal nociceptive system. Methods: Neuropeptide release, calcium imaging and meningeal blood flow recordings were applied in rodent models of meningeal nociception to clarify possible receptor mechanisms underlying these pain phenomena. Results: Phenylephrine above 10 mM dose-dependently released calcitonin gene-related peptide (CGRP) from the dura mater and isolated trigeminal ganglia, whereas hyperosmotic mannitol at 90 mM was ineffective. The phenylephrine-evoked release was blocked by the transient receptor potential vanilloid 1 (TRPV1) antagonist BCTC and did not occur in trigeminal ganglia of TRPV1-deficient mice. Phenylephrine at 30 mM caused calcium transients in cultured trigeminal ganglion neurons responding to the TRPV1 agonist capsaicin and in HEK293T cells expressing human TRPV1. Local application of phenylephrine at micromolar concentrations to the exposed rat dura mater reduced meningeal blood flow, whereas concentrations above 10 mM caused increased meningeal blood flow. The flow increase was abolished by pre-application of the CGRP receptor antagonist CGRP8-37 or the TRPV1 antagonist BCTC. Conclusions: Phenylephrine at high millimolar concentrations activates TRPV1 receptor channels of perivascular afferents and, upon calcium inflow, releases CGRP, which increases meningeal blood flow. Activation of TRPV1 receptors may underlie trigeminal nociception leading to cranial pain such as local burning sensations or headaches caused by administration of high doses of phenylephrine. Significance: Phenylephrine is used at high concentrations as a mydriaticum and for treating nasal congestion. As adverse side-effects burning sensations and headaches have been described. Phenylephrine at high concentrations causes calcium transients in trigeminal afferents, CGRP release and increased meningeal blood flow upon activation of TRPV1 receptor channels, which is likely underlying the reported pain phenomena.
CRIS-Team Scopus Importer:2019-12-03

High-dose phenylephrine increases meningeal blood flow through TRPV1 receptor activation and release of calcitonin gene-related peptide - Dux, Maria; Babes, Alexandru; Manchen, Jessica; Sertel-Nakajima, Julika; Vogler, Birgit; Schramm, Jana; Meßlinger, Karl (European Journal of Pain, 2020)
BACKGROUND: The α1 -adrenoceptor agonist, phenylephrine, is used at high concentrations as a mydriatic agent and for the treatment of nasal congestion. Among its adverse side-effects transient burning sensations are reported indicating activation of the trigeminal nociceptive system. METHODS: Neuropeptide release, calcium imaging and meningeal blood flow recordings were applied in rodent models of meningeal nociception to clarify possible receptor mechanisms underlying these pain phenomena. RESULTS: Phenylephrine above 10 mM dose-dependently released calcitonin gene-related peptide (CGRP) from the dura mater and isolated trigeminal ganglia, whereas hyperosmotic mannitol at 90 mM was ineffective. The phenylephrine-evoked release was blocked by the transient receptor potential vanilloid 1 (TRPV1) antagonist BCTC and did not occur in trigeminal ganglia of TRPV1-deficient mice. Phenylephrine at 30 mM caused calcium transients in cultured trigeminal ganglion neurons responding to the TRPV1 agonist capsaicin and in HEK293T cells expressing human TRPV1. Local application of phenylephrine at micromolar concentrations to the exposed rat dura mater reduced meningeal blood flow, whereas concentrations above 10 mM caused increased meningeal blood flow. The flow increase was abolished by pre-application of the CGRP receptor antagonist CGRP8-37 or the TRPV1 antagonist BCTC. CONCLUSIONS: Phenylephrine at high millimolar concentrations activates TRPV1 receptor channels of perivascular afferents and, upon calcium inflow, releases CGRP, which increases meningeal blood flow. Activation of TRPV1 receptors may underlie trigeminal nociception leading to cranial pain such as local burning sensations or headaches caused by administration of high doses of phenylephrine. SIGNIFICANCE: Phenylephrine is used at high concentrations as a mydriaticum and for treating nasal congestion. As adverse side-effects burning sensations and headaches have been described. Phenylephrine at high concentrations causes calcium transients in trigeminal afferents, CGRP release and increased meningeal blood flow upon activation of TRPV1 receptor channels, which is likely underlying the reported pain phenomena.
EVALuna2:213473